THE CURRICULAR ADAPTATIONS AND THE IMPORTANCE OF SUPPORT OF THE TEACHER - Oliveira Bezerra, Ana Maria de [UNESP]; Xavier Fonseca-Janes, Cristiane Regina [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2015)
The enrollment of the target group of Special Education students in public schools does not guarantee the effectuation of inclusive education. They need access to an adapted curriculum aiming the development of their potential. The aim of this study was to analyze whether the adapted curriculum materials are performed at regular rooms for students with intellectual disability; watch the strategic actions and analyze whether the regular education teachers can count on the help of an employee from the Centre for Support and Service Inclusion (SAAI). Data were collected in two classrooms in a prefecture's school in Sao Paulo city. This procedure occurred through a protocol of observation and interviews with the teachers. The results showed that there is a discrepancy in the teachers' actions in relation to curricular adaptations and interactions with the intellectual disability student. The interviewed ones agree that there is no specific time for orientation meetings with the teacher from SAAI.
Keywords: Curriculum adaptation; Inclusive education; Special education; Intellectual Disability